Alexithymia and emotional empathy following traumatic brain injury - Claire Williams (Journal of Clinical and Experimental Neuropsychology, 2009)
The frequency of alexithymia and the proportion of cases reporting low emotional empathy after traumatic brain injury (TBI) were compared with a control group. The study also examined the relationship between alexithymia and emotional empathy, controlling for the influence of cognitive ability, severity of head injury, and time since injury. A total of 64 TBI patients and matched controls completed the 20-Item Toronto Alexithymia Scale (TAS-20) and Balanced Emotional Empathy Scale (BEES). The TBI group exhibited a significantly higher frequency of alexithymia (60.9%) and low emotional empathy (64.4%) than did the control group (10.9% and 34.4%). Significant moderate negative correlations were found between TAS-20 and BEES scores, with TAS-20 total scores accounting for a significant amount of variance in BEES scores. However, no significant correlation was obtained between Subscale 1 of the TAS-20 (difficulty identifying feelings) and BEES scores in the TBI group. Additionally, there were no significant relationships between alexithymia, emotional empathy, injury severity, and time since injury. The results suggest an inverse relationship between alexithymia and emotional empathy.